IMPLEMENTASI KEBIJAKAN PENGELOLAAN DISTRIBUSI PUPUK DAN RESPONS MASYARAKAT TERHADAP KELANGKAAN PUPUK BERSUBSIDI DI DESA SUGIHAN KECAMATAN MERAKURAK KABUPATEN TUBAN TAHUN 2022 (Jurnal Nawala Politika, 2023)
This study aims to determine the implementation of subsidized fertilizer policies and community responses related to the scarcity of subsidized fertilizers in Sugihan village, Merakurak district, Tuban regency. Merille S. Grindle's theory of policy implementation is used to analyze the success of a policy whether or not it is successful in terms of the content and context of subsidized fertilizer policies, in addition to that joel S. Mighdal's Theory of State in Society is used to analyze the ability of the government as a policy maker who is unable to provide appropriate sanctions due to the limitations of the government. By using qualitative research methods through interviews, the conclusions of the research results were obtained, namely the procurement and distribution of subsidized fertilizers has been regulated in Permendag number 15 / M-DAG / Per / 4/2013 administratively but in Sugihan village it violates the rules of the government, namely farmer groups sell outside the regional zone and outside the members of their farmer groups and Tuban Regent Decree number 188.45/12/KPTS/414.012/2022 concerning Allocation and HET for the agricultural sector of Tuban regency, the amount of procurement that is not in accordance with the realization causes scarcity and gets a response from the loby farmer elite directly to hoard subsidized fertilizer and this is used by the head of the farmer group to sell fertilizer prices above HET. Keywords: Implementation, Distribution, Community Respons, Subsidized Fertilizer